Influence of different periods of pre-slaughter fasting on microbiological quality of bullfrog carcasses (Lithobates catesbeianus) - Costa, P.c.; Nascimento, Y.f. [UNESP]; Costa, L.r.m. [UNESP]; Dias, S.c. [UNESP]; Ventura, N.k.o.; Yamatogi, R.s.; Costa, F.a.a.; Cossi, M.v.c. (Universidade Federal de Minas Gerais, Escola de Veterinária, 2021)
The aim of this study was to evaluate the influence of different periods of pre-slaughter fasting (F1: 2 to 24 hours and F2: 48 to 72 hours) on the counts of hygiene indicator microorganisms and the presence of Salmonella spp. in carcasses of bullfrogs. Two different stages of the slaughter process were analyzed: after bleeding (A) and after the final carcasses cleaning (B). Samples from each fasting period were analyzed to count hygiene indicator microorganisms (n=30) and Salmonella spp. (n=140). For aerobic mesophilic microorganisms, the variation in fasting periods caused a reduction of 0.69 log10 CFU / g (P<0.05) in F2 when compared to F1 at point B of the slaughter. Coliforms at 35º C and Escherichia coli showed no differences (P >0.05) between the fasting analyzed periods. Considering the presence of E. coli, it was observed that F2 resulted in a reduction of 30% (P<0.05) positivity on point B. For Salmonella spp., the results showed that F2 contributed to an 11.5% reduction in the presence of this bacteria at point B. (P<0.05). Therefore, it is concluded that 48 to 72 hours of pre-slaughter fasting resulted in a positive impact on the microbiological quality of bullfrog carcasses.

O objetivo deste estudo foi avaliar a influência de diferentes períodos de jejum pré-abate (F1: duas a 24 horas e F2: 48 a 72 horas) nas contagens de micro-organismos indicadores de higiene e na presença de Salmonella spp. em carcaças de rãs-touro. Foram analisadas duas etapas do processo de abate: após a sangria (A) e após a toalete final da carcaça (B). As amostras de cada período de jejum foram utilizadas para contagem de indicadores de higiene (n = 30) e Salmonella spp. (n = 140). Para aeróbios mesófilos, a variação no tempo de jejum causou uma redução de 0,69 log10 UFC/g (P<0,05) em F2 quando comparado a F1 na etapa B do abate. Os coliformes a 35ºC e Escherichia coli não apresentaram diferenças (P>0,05) entre os dois períodos de jejum analisados. Considerando a presença de E. coli, F2 resultou em uma redução de 30% (P<0,05) de positividade na etapa B. Para Salmonella spp., os resultados mostraram que F2 contribuiu para uma redução de 11,5% na presença desse micro-organismo na etapa B. Portanto, conclui-se que 48 a 72 horas de jejum pré-abate tiveram um impacto positivo na qualidade microbiológica das carcaças de rã-touro.
[Influência de diferentes períodos de jejum pré-abate na qualidade microbiológica de carcaças de rã-touro (Lithobates catesbeianus)]
Keywords: food safety; hygiene indicator; Salmonella spp; indicador de higiene; Salmonella spp; segurança de alimentos